4-Hydroxyderricin and xanthoangelol isolated from Angelica keiskei prevent dexamethasone-induced muscle loss. Issue 6 (8th June 2020) - Yoshioka, Yasukiyo; Samukawa, Yumi; Yamashita, Yoko; Ashida, Hitoshi
Abstract : 4-Hydroxyderricin and xanthoangelol are shown to prevent dexamethasone-induced muscle loss by inhibiting protein degradation through glucocorticoid receptor pathway and p38/FoxO3a pathway. Abstract : Since a decrease in muscle mass leads to an increased risk of mortality, the prevention of muscle wasting contributes to maintaining the quality of life. Recently, we reported that glabridin, a prenylated flavonoid in licorice, prevents dexamethasone-induced muscle loss. In this study, we focused on the other prenylated chalcones 4-hydroxyderricin and xanthoangelol in Ashitaba ( Angelica keiskei ) and investigated their prevention effect on dexamethasone-induced muscle loss. It was found that 4-hydroxyderricin and xanthoangelol significantly prevented dexamethasone-induced protein degradation in C2C12 myotubes by suppressing the expression of ubiquitin ligases, Cbl-b and MuRF-1. These prenylated chalcones acted as the antagonists of the glucocorticoid receptor and inhibited the binding of dexamethasone to this receptor and its subsequent nuclear translocation. In addition, the chalcones suppressed the phosphorylation of p38 and FoxO3a as the upstream factors for ubiquitin ligases. Dexamethasone-induced protein degradation and upregulation of Cbl-b were attenuated by the knockdown of the glucocorticoid receptor but not by the knockdown of p38. In male C57BL/6J mice, the Ashitaba extract, containing 4-hydroxyderricin and xanthoangelol, suppressed dexamethasone-induced muscle mass wasting accompanied by a decrease in the expression of ubiquitin ligases by inhibiting the nuclear translocation of the glucocorticoid receptor and phosphorylation of FoxO3a. In conclusion, 4-hydroxyderricin and xanthoangelol are effective compounds to inhibit steroid-induced muscle loss.